Structure and properties of Brazilian peat: Analysis by spectroscopy and microscopy - Romão, Luciane P. C.; Lead, Jamie R.; Rocha, Julio C. [UNESP]; De Oliveira, Luciana Camargo [UNESP]; Rosa, André H. [UNESP]; Mendonça, André G. R. [UNESP]; Ribeiro, Adauto de Souza (FapUNIFESP (SciELO), 2007)
Peat was taken from the Sergipe State, Brazil and characterized by several techniques: elemental and thermal analyses; Fourier infrared (FTIR) and solid state 13C nuclear magnetic resonance (NMR) spectroscopies; scanning electron microscopy (SEM), environmental scanning electron microscopy (ESEM) and X-ray diffractometry (XRD). Also, the Sergipe State peat samples were compared with other peat sample from later from Sao Paulo State, Brazil. The lowest O/C and E 4/E 6 ratios and differential thermal analysis (DTA) curves of the Santo Amaro (SAO) sample indicated that this sample had the highest degree of decomposition. FTIR results showed that Itabaiana (ITA) and São Paulo (SAP) samples presented more prominent peak at 1086 cm -1 attributed the presence of Si-O than SAO sample spectra. The SAO sample showed two more intense peaks at 2920 cm -1 and 2850 cm -1. These results were corroborated by 13C NMR and thermal gravimetric (TG) where the relative abundance of the alkyl-C groups was greater in the SAO sample. The X-ray diffractometry (XRD) of SAO sample is characteristic of amorphous matter however, the SAP and ITA samples revealed the large presence of quartz mineral. The scanning electron microscopy (SEM) and environmental scanning electron microscopy (ESEM) showed that the surface of peat samples have porous granules of organic material. The ITA and SAP peat samples are alike while SAO peat sample is richer in organic material. Only the SAO sample has truthful characteristics of peat. The results of this study showed that the samples are very different due to variable inorganic and organic material contents. ©2007 Sociedade Brasileira de Química.
Keywords: Environmental scanning electron microscopy; Peat structure and properties; Scanning electron microscopy; Spectroscopy and microscopy characterization